A Graphical Method to Evaluate Exposure-Response Relationships in Epidemiologic Studies Using Standardized Mortality or Morbidity Ratios - Edwin van Wijngaarden Ph.D (SAGE Publishing, 2005)
In occupational epidemiology, exposure-response analyses play an important role in the evaluation of the etiologic relevance of chemical and physical exposures. The standardized mortality or morbidity ratio (SMR) has been commonly used in occupational cohort studies. Statistical approaches to evaluate exposure-response patterns using SMRs have mostly been limited to analyses in which the exposure under investigation is categorized. Here, a graphical method for evaluating exposure-response patterns is presented based on SMR estimates across moving exposure windows. This method is demonstrated using the results of two hypothetical cohort studies. The proposed approach may be useful for graphical exploration of exposure-response trends in situations where the number of observed cases is small.